Validation of Active Surveillance Testing for Clostridium difficile Colonization Using the cobas Cdiff Test - Patel, Parul A. (J Clin Microbiol, 2018)
Clostridium difficile infection (CDI) is not declining in the United States. Nucleic acid amplification tests (NAAT) are used as part of active surveillance testing programs to prevent health care-associated infection. The objective of this study was to validate the cobas Cdiff Test on the cobas 4800 System (cobas) within a four-hospital system using prospectively collected perirectal swabs from asymptomatic patients at admission and during monthly intensive care unit (ICU) screening in an infection control CDI reduction program. Performance of the cobas was compared to that of toxigenic culture. Each positive cobas sample and the next following negative patient swab were cultured. The study design gave 273 samples processed by both cobas (137 positive and 136 negative) and culture (one negative swab was not cultured). Discrepant analysis was performed using a second NAAT, the Xpert C. difficile Epi test (Xpert). This strategy was compared to a medical record review for antibiotic receipt that would inhibit growth of C. difficile in colonic stool. None of the cobas-negative samples were culture positive. The cobas positive predictive value was 75.2% (95% confidence interval [CI], 66.9% to 82%) and positive percent agreement was 100% (95% CI, 96.0% to 100%). Overall agreement between cobas and direct toxigenic culture was 87.6% (95% CI, 83.1% to 91%). For the cobas-positive/culture-negative (discrepant) samples, 7 Xpert-positive samples were from patients receiving inhibitory antimicrobials; only 4 of 23 Xpert-negative samples received these agents (P = 0.00006). Our results support use of the cobas as a reliable assay for an active surveillance testing program to detect asymptomatic carriers of toxigenic C. difficile.